2022
DOI: 10.3390/cells11142155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TP53 Mutations and miRs on Immune Responses in the Tumor Microenvironment Important in Pancreatic Cancer Progression

Abstract: Approximately 90% of pancreatic cancers are pancreatic ductal adenocarcinomas (PDAC). PDAC is the fourth leading cause of cancer death world-wide. Therapies for PDAC are largely ineffective due to the dense desmoplastic tumor microenvironment which prevents chemotherapeutic drugs and small molecule inhibitors from exerting effective anti-cancer effects. In this review, we will discuss the roles of TP53 and miRs on the PDAC tumor microenvironment and how loss of the normal functions of TP53 promote tumor progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 200 publications
0
15
0
Order By: Relevance
“…Mutations in KRAS can disrupt the switch between active and inactive states thus promoting cancer development ( 39 ). Virtually all PDAC tumors harbor KRAS mutations and a majority also have mutations in P53, a tumor suppressor protein ( 3 , 40 ). Therefore, we investigated whether GAS M1 strain had similar anti-tumor effects using KPCY6422c1 cells (abbreviated as KPC), a PDAC tumor lineage that mirrors the genetics of human PDAC ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in KRAS can disrupt the switch between active and inactive states thus promoting cancer development ( 39 ). Virtually all PDAC tumors harbor KRAS mutations and a majority also have mutations in P53, a tumor suppressor protein ( 3 , 40 ). Therefore, we investigated whether GAS M1 strain had similar anti-tumor effects using KPCY6422c1 cells (abbreviated as KPC), a PDAC tumor lineage that mirrors the genetics of human PDAC ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Events initiated by KRAS mutations, such as cellular autophagy, changes in metabolism, and continuous activation of the yes-associated protein pathway, combine to result in immune evasion [ 44 ]. Mut-TP53 can accelerate tumor progression and metastasis by triggering immunosuppressive properties of the PAAD [ 45 , 46 ]. The TGF-β pathway mediated by SMAD4 suppresses the immune system response, assisting tumor cells in evading immune reactions [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, TP53 mutation can lead to cancer in humans. TP53 mutations are most frequently missense mutations concentrated in the DNA-binding domain between codons 125 and 300 and occur in almost all types of cancer, including pancreatic cancer, ovarian cancer, esophageal cancer, colorectal cancer, head and neck cancer, laryngeal cancer and lung cancer ( Olivier et al, 2010 ; Peltonen et al, 2010 ; Mogi and Kuwano, 2011 ; Yurgelun et al, 2015 ; Silwal-Pandit et al, 2017 ; McCubrey et al, 2022 ). Our study found that the expression levels of SUMO family members were significantly increased in PAAD tissues with TP53 mutations compared with PAAD with wild-type TP53, suggesting that SUMO family members may be downstream targets of mutant TP53.…”
Section: Discussionmentioning
confidence: 99%